Accounting Information System Design For Kopitiam Utama Rasa - Jennifer Jennifer; Anita Anita (Universitas Internasional Batam, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a strategic pillar for the Indonesian economy, contributing significanly the national GDP and workforce absoroption. However, MSMEs optimization is often hindered by poor internal governance, particularly inadequate financial management. Kopitiam Utama Rasa exemplifies an MSMEs still using inefficient manual recording system. This community service project aimed to address this constraint by designing and implementing a digital accounting system built on Microsoft Excel. The system encompasses essential modules such as COA, inventory, transaction form, and others. The result show that the digital system successfully enhanced the accuracy, efficiency, and effectiveness of Kopitiam Utama Rasa’s financial reporting. With the structured system in place, the owner can now obtain accurate and timely financial information, which is crucial for precise performance assessment and long-term business viability.